Exosome-Mediated Metastasis: Communication from a Distance - Wortzel, Inbal; Dror, Shani; Kenific, Candia M.; Lyden, David (Developmental cell, 2019)
Metastasis, a critical phase of tumor progression, remains a primary challenge in treating cancer and a major cause of cancer mortality. Cell-cell communication via extracellular vesicles (exosomes and microvesicles) between primary tumor cells and the microenvironment of distant organs is crucial for pre-metastatic niche (PMN) formation and metastasis. Here, we review work on the contribution of exosome cargo to cancer progression, the role of exosomes in PMN establishment, and the function of exosomes in organotropic metastasis. We also describe the clinical utility of exosomes. Metastasis remains a primary challenge in treating cancer. Exosome-mediated communication between primary tumor cells and the microenvironment of distant organs is crucial for pre-metastatic niche formation and metastasis. In this Review, Wortzel et al. consider the contribution of exosome cargos to cancer progression and describe their potential clinical utility.